In vitro methods to determine the antioxidant activity of caffeic acid - Spagnol, Caroline Magnani; Assis, Renata Pires; Brunetti, Iguatemy Lourenço; Isaac, Vera Lucia Borges; Salgado, Hérida Regina Nunes; Corrêa, Marcos Antonio (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2019)
Caffeic acid (CA) is a plant metabolite acting as a carcinogenic inhibitor, and exhibits a high antioxidant effect and some antimicrobial activity. Besides, this compound can be useful in the prevention of heart diseases and atherosclerosis, among others. The present study aims to determine the in vitro antioxidant activity of CA in order to increase the frequency of its use and reliability in the prevention of damage caused by free radicals and other reactive species. The tests performed were as follows: Radical anion superoxide capture; crocin bleaching assay; capturing ability of hypochlorous acid; H2O2 capture; capturing capacity of the ABTS•+/DPPH•; and SOD-like activity. The values of the CA antioxidant activity were very close to the values of standards in all tests. Besides, CA presented an antioxidant activity greater than that of ascorbic acid and trolox, and its advantages include higher stability than ascorbic acid and extraction from natural sources, as opposed to trolox. [Display omitted] •Investigation of caffeic acid antioxidant activity.•Caffeic acid for prevention of damage caused by free radicals.•Caffeic acid antioxidant activity was very close to the standards in all tests.•Caffeic acid presented antioxidant activity greater then ascorbic acid and trolox.